Experimental assessment of scale-effects on the aerodynamic characterization of a transitionally-operating airfoil working under clean flow conditions. (January 2022) - Zarketa-Astigarraga, Ander; Penalba, Markel; Martin-Mayor, Alain; Martinez-Agirre, Manex
Abstract: Wind tunnel tests are carried out upon a NACA0021 airfoil subjected to transitional Reynolds numbers. Transitionally-operating airfoils show a high sensitivity to external conditions and pose relevant measurement issues for capturing the physical processes adequately. On the global side, the employed set of techniques measures lift forces directly and uses the momentum-deficit method for drag coefficients. Locally, the development of transitional structures is acknowledged via surface pressure measurements carried out by pressure taps together with oil-flow visualizations. The coupling of such techniques with a well-founded uncertainty analysis shows two relevant aspects of the measurement protocolization: on the one hand, the limitations of either the global or local methods for completely accounting for all transitional phenomena. On the other hand, the fact that combining the proposed set of different measurement techniques with a systematic protocol is a mandatory requirement for achieving a holistic characterization of transitionally-operating airfoils. Highlights: Load and pressure measurements, momentum-deficit method and oil-flow visualizations. Uncertainty analysis addresses scale-effect on transitionally-operating airfoils. Limitations of the piezoelectric balance for carrying aerodynamic drag measurements. Surface pressure measurements and oil-flow visualizations limited to local analysis. Different measurement techniques for performing a thorough aerodynamic characterization.